Spatial Non-Compliance and Ecosystem Risk of Service-Station Proliferation in a Densely Populated Tropical Megacity District: A GIS-Based Assessment of Funa, Kinshasa (DR Congo) - Kumbu Ngoma Gautier; Vuni Simbu Alexis; Mayala Tshiamu Héritier; Ntombi Mwen Mutsindu Abel; Losembe Konga Moïse; Lemfu Emmanuel; Umba Siasi Victorine; Fils Makanzu Imwangana; N'zau Umba-di-Mbudi Clement (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Unregulated proliferation of open-air service (petrol) stations in Kinshasa, Democratic Republic of the Congo, poses ecosystem and public-health risks through soil, water and air pollution, fire, and chronic exposure to carcinogenic volatile hydrocarbons. Objective: This study assessed compliance of station siting with separation-distance standards and quantified the resulting spatial risk in the Funa pilot district. Methods: Twenty-four stations were geolocated by GPS (2019–2023); Euclidean distances to the nearest dwelling, school, church and hospital, and to the nearest neighbouring station, were computed in a GIS and analysed by one-way ANOVA with Tukey HSD, Pearson correlation, regression and principal component analysis, then synthesised in a composite Spatial Encroachment Risk Index (SERI). Results: Mean station-to-dwelling distance was 21.8 ± 7.8 m, with no station meeting the 50 m minimum; mean distances to schools (157.8 ± 48.5 m), churches (127.9 ± 42.2 m) and hospitals (286.7 ± 103.0 m) all fell below the 500 m standard (0% compliance), and only 20.8% met the 500 m inter-station criterion. Distances differed by receptor class (F(3,92) = 77.07, p < 0.001, η² = 0.715), and newer stations were sited closer to receptors (hospitals r = −0.745, p < 0.001); 21 of 24 stations were High or Very High risk. Conclusion: Total non-compliance demonstrates an urgent need for a specific siting decree and an accompanying layout manual to protect the urban ecosystem and population health.